Principal's Strategy to Improve the Quality of Islamic Education Institutions - Mafaza, Sartika; Rahmi, Elvi (STIT Ahlussunnah Bukittinggi, 2024)
The quality of Islamic educational institutions is greatly influenced by the effectiveness of the principal's leadership in managing and developing all components of education. This study aims to analyze in depth the strategies implemented by the principal in an effort to improve the quality of Islamic educational institutions, both from the managerial, academic, and spiritual aspects. The main focus of this study is how the principal prepares strategic planning, starting from the recruitment system for educators and education personnel, development and evaluation of the performance of educators and education personnel. at Insan Kamil, Bukittinggi City. This study uses a qualitative method with the typefield research. Data sources using observation, interviews and documentation, data sources in this study are the head of the foundation, principal, vice principal, ustadz and ustadzah Insan Kamil. The results of the study indicate that: 1) The recruitment system for educators and education personnel at Insan Kamil has been implemented because it has compiled a recruitment system starting from applicant administration, applicant criteria and applicant recruitment system. 2) The development of educators and education personnel has been implemented both through classical and non-classical channels because activities such as seminars, workshops, webinars, comparative studies and outbound have been carried out. 3) Evaluation of the performance of educators and education personnel has been implemented because at the beginning of the semester educators have prepared learning administration and held an evaluation meeting at the end of the semester, to review the learning process that has been carried out during the semester. The results of this study can be used as initial data for subsequent researchers in studying this problem in different contexts and issues.